Syntaxin 17 Translocation Mediated Mitophagy Switching Drives Hyperglycemia‐Induced Vascular Injury - Luo, Anqi; Wang, Rui; Gong, Jingwen; Wang, Shuting; Yun, Chuan; Chen, Zongcun; Jiang, Yanan; Liu, Xiaoquan; Dai, Haofu; Liu, Haochen; Zheng, Yunsi (Advanced science, 2025)
The risk of diabetic cardiovascular complications is closely linked to the length of hyperglycemia exposure. Mitophagy plays a significant role in vascular endothelial injury. However, the specific mechanisms by which mitophagy contributes to endothelial injury during sustained hyperglycemia remain unclear. In diabetic ApoE−/− mice and human umbilical vein endothelial cell (HUVEC) models, mitophagy is enhanced following short‐term and long‐term high‐glucose exposure. Short‐term high‐glucose exposure promotes Parkin‐mediated mitophagy and upregulates mitochondrial fission protein 1 (Fis1) expression, whereas long‐term high‐glucose exposure suppresses Parkin‐mediated mitophagy and downregulates Fis1. With prolonged high‐glucose exposure, Syntaxin 17 (STX17) translocates from the endoplasmic reticulum to the mitochondria, activating STX17‐mediated mitophagy. Silencing STX17 alleviates mitochondrial degradation, decreases reactive oxygen species (ROS) levels, enhances endothelial nitric oxide synthase (eNOS) phosphorylation, and reduces apoptosis. Silencing Fis1 accelerates the switching to STX17‐mediated mitophagy, worsening endothelial dysfunction, whereas Fis1 overexpression prevents this switching, reducing ROS and apoptosis and enhancing eNOS phosphorylation. In summary, these findings suggest that the switching from Parkin‐mediated to STX17‐mediated mitophagy drives vascular endothelial injury following long‐term hyperglycemic exposure, providing valuable insights into therapeutic strategies for diabetic cardiovascular complications. Mitophagy switching drives high‐glucose‐induced vascular endothelial injury. Short‐term high‐glucose exposure upregulates Fis1 expression and enhances Fis1‐TBC1D15 interaction, activating Parkin‐mediated mitophagy. Long‐term high‐glucose exposure reduces Fis1 expression, inhibiting Parkin‐mediated mitophagy and triggering mitophagy switching from Parkin‐mediated to STX17‐mediated mitophagy, leading to vascular endothelial injury. Preventing mitophagy switching may be a promising approach to alleviate high‐glucose‐induced vascular endothelial injury.